Simultaneous bioconversion of gelatinized starchy waste from the rice noodle manufacturing process to lactic acid and maltose-forming α-amylase by Lactobacillus plantarum S21, using a low-cost medium - Kridsada Unban (2019)
© 2019 by the authors. A direct bioconversion of gelatinized starchy waste (GSW) to lactic acid by amylolytic lactic acid bacterium Lactobacillus plantarum S21 was investigated. Corn steep liquor (CSL) was selected as the most suitable low-cost nitrogen source for replacing yeast extract, beef extract, and peptone in De Man, Rogosa and Sharpe (MRS) medium. Plackett–Burman design results indicated that GSW and CSL were the two most nutrients that significantly influence lactic acid production, among eight medium components, including GSW, CSL, K2HPO4, CH3COONa, (NH4)2HC6H5O7, MgSO4, MnSO4, and Tween 80. A new low-cost medium containing only GSW (134.4 g/L) and CSL (187.7 g/L) was achieved as omitting other six components from the optimized medium had no effect on lactic acid yield. Batch fermentation at 37°C both in 1 L and 10 L jar fermenters showed non-significantly different productivity. A by-product, maltose-forming α-amylase, was successfully achieved up to 96% recovery yield using an ultrafiltration unit equipped with a 50 kDa cut-off membrane. Crude lactic acid exhibited the additional benefit of antimicrobial activity against food and feed pathogens Salmonella enterica serovar Typhimurium TISTR 292, Vibrio cholerae TH-001, and also E. coli ATCC 25922. This study presents a promising bioprocess for the simultaneous production of lactic acid, and a value-added food enzyme, using only two industrial wastes, GSW and CSL, as the medium components.